Peliosis hepatis associated with lymphoplasmacytic lymphoma - An autopsy case report - Corpa, MVN; Bacchi, M. M.; Bacchi, C. E.; Coelho, Kunie Iabuki Rabello [UNESP] (College Amer Pathologists, 2004)
A 72-year-old man with no previous history of liver disease was admitted to our university hospital with severe dyspnea, edema of the lower limbs, and weight loss. Within a few days of hospitalization, he died due to severe bleeding in the upper digestive tract. At autopsy, the liver displayed typical gross features of peliosis hepatis. in addition, a diffuse infiltration of liver, spleen, bone marrow, and lymph nodes by lymphoplasmacytic lymphoma was disclosed by light microscopy. In the liver, the neoplastic cells partially filled the peliotic cavities. Peliosis hepatis is a rare liver disease characterized by multiple blood-filled, dilated cavities within the liver parenchyma. Association of lymphoplasmacytic lymphoma and peliosis hepatis has rarely been reported in the literature. The pathologic findings of such an unusual association and a review of the literature are presented.